Implementation of assembly sequence by arduino and monitoring system using ni myrio - Wong, Choon Chen (2015)
Nowadays, microcontroller is widely used in most of the industries especially in assembly line because of its advantage in assembly sequence and the easiness to control it. However, the user needs to control the assembly sequence of the production in order to have faster respond that control by the controller. Hence, the assembly sequence of the production can be implement by using the microcontroller that able to control the motor or even can control without workmanship. Besides that, the whole assembly process can be monitor by using the latest microprocessor, with higher processing rate that able to let the image captured from the camera more clear and precise. The user able to control the position of the camera, capture and record the data during the assembly process by using the high technology in this new globalization. To be more advance ,the user also able to save and play the recorded image/video if they choose the options given inside the interface (GUI) and can choose the program that help to analyze the products.